Digital Transformation and Sustainability: A Multidisciplinary Analysis of the Impact of Artificial Intelligence in Education, Business, and Healthcare - Ifan Syifauddin (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
Digital transformation has become a key driver in shaping sustainability across various sectors. The development of Artificial Intelligence (AI) has brought significant impacts on education, business, and healthcare. This study aims to provide a multidisciplinary analysis of how AI contributes to efficiency, innovation, and sustainability. In education, AI enables opportunities through personalized learning and improved accessibility. In business, it fosters optimization in management, marketing strategies, and operational efficiency. Meanwhile, in healthcare, AI contributes to enhanced diagnostic accuracy, patient data management, and more effective services. This research adopts a descriptive qualitative approach by reviewing recent literature and case studies of AI implementation in the three sectors. The findings reveal that AI not only accelerates digital transformation but also serves as a fundamental pillar in supporting sustainable practices. Nevertheless, its implementation faces challenges related to ethics, regulation, and unequal access to technology. Therefore, this study emphasizes that AI integration should be accompanied by inclusive governance and a long-term sustainability orientation.